1997
DOI: 10.1002/adma.19970090611
|View full text |Cite
|
Sign up to set email alerts
|

Access in mesoporous materials: Advantages of a uniform pore structure in the design of a heavy metal ion adsorbent for environmental remediation

Abstract: Communications ADVANCED MATERIALSWe have shown that computational simulations, based on relatively simple models and simulation procedures, provide an effective procedure for rationalizing the orientation of guest species within layered double hydroxides. The results are in good agreement with those of experiment and suggest that further modeling of these materials would be beneficial.The preparation of improved adsorbent materials that can remove toxic metal ions from aqueous media is a continuing objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
445
1
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(473 citation statements)
references
References 12 publications
17
445
1
3
Order By: Relevance
“…For sake of comparison, silica gels and MTS silica samples displaying different pore size, grafted with thiol groups, have been examined. The surfactant-templated mesostructure with well-defined large diameter channels (MPS-SBA15-S60) revealed 100% accessibility: its Hg II loading capacity was identical to the amount of SH groups in the material (1.0 mmol g À1 ), in agreement with the 1 : 1 stoechiometry reported for the Hg II /SH complex system [38,39]. By contrast, the adsorption capacity of the correspondingly grafted amorphous silica gel displaying the same average pore size (MPS-K60) was notably lower, with saturation observed at 87% filling.…”
Section: àsupporting
confidence: 74%
See 1 more Smart Citation
“…For sake of comparison, silica gels and MTS silica samples displaying different pore size, grafted with thiol groups, have been examined. The surfactant-templated mesostructure with well-defined large diameter channels (MPS-SBA15-S60) revealed 100% accessibility: its Hg II loading capacity was identical to the amount of SH groups in the material (1.0 mmol g À1 ), in agreement with the 1 : 1 stoechiometry reported for the Hg II /SH complex system [38,39]. By contrast, the adsorption capacity of the correspondingly grafted amorphous silica gel displaying the same average pore size (MPS-K60) was notably lower, with saturation observed at 87% filling.…”
Section: àsupporting
confidence: 74%
“…In particular, MTS-bound thiol functions were effective immobilized ligands for uptake of mercury(II) species from aqueous solutions and displayed better accessibility to the binding sites than the corresponding amorphous materials [38 ± 44]. This enhancement was ascribed to the regular structure of the ordered materials contrary to the amorphous solids in which pore blockage limits the access of metal ions to few percents of the complexing sites [38,39]. Similar effects were observed with mesoporous solids containing phosphorous centers [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods involves preparing the films and then backfilling the pores with the desired molecules. [78][79][80][81][82][83][84][85] When the molecules contain alkoxysilane groups, they can be used to functionalize the newly exposed pore surfaces. For instance, the entrapment of lanthanide complexes into surface-modified mesoporous silica (MCM41, MCM48 and SBA15) by a two-step procedure has been widely studied.…”
Section: Luminescence Of Lanthanide Ions As a Probe In Mesostructuredmentioning
confidence: 99%
“…The use of hybrid precursors has attracted the attention of the scientific community because the presence of functional groups can be important in sorption and release of bioactive molecules, [23][24][25] purifications, [26][27][28][29][30][31][32][33] analytical 34,35 and optical 36,37 applications. In particular, it has been suggested that functionalizing mesoporous materials with amine groups can be useful for CO 2 capture and separations.…”
Section: -22mentioning
confidence: 99%